The Determinants of Family Takaful Demand in Pakistan - Dr. Samina Riaz, Dr. Qasim Saleem, Dr. Hafiz Muhammad Ishaq, Dr. Ramaisa Aqdas (Hamdard Islamicus, 2021)
The Holy Qur’Én in its many commands and the ×adÊth of ×aÌrat Muhammad RasËlullah KhÉtam un NabiyyÊn Øallallahu ‘alaihi wa ‘alÉ Ólihi wa AÎÍÉbihi wa Øallam amplify the importance of parenting. Having said that, the same Holy Qur’Én and the ×adÊth also emphasize the individuality of a child daughter or son, and underline that they are fullfledged individuals, unique and full of potential. She/he has similar rights that Islam grants to an adult. It has been observed that some Muslim parents overlook the autonomy and sensitivities of their children as they enforce their thoughts, choices and outlook of life on their children. The present paper aims to highlight that Islam does not overlook individuality of a child and envisage counseling more than authoritarian parenting.